2016 IEEE Winter Conference on Applications of Computer Vision (WACV) 2016
DOI: 10.1109/wacv.2016.7477555
|View full text |Cite
|
Sign up to set email alerts
|

Face recognition using deep multi-pose representations

Abstract: We introduce our method and system for face recognition using multiple pose-aware deep learning models. In our representation, a face image is processed by several posespecific deep convolutional neural network (CNN) models to generate multiple pose-specific features. 3D rendering is used to generate multiple face poses from the input image. Sensitivity of the recognition system to pose variations is reduced since we use an ensemble of pose-specific CNN features. The paper presents extensive experimental resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(73 citation statements)
references
References 23 publications
(66 reference statements)
1
72
0
Order By: Relevance
“…For face identification, a major accomplishment of DCNNs is their visual robustness to changes in viewpoint, illumination, expression, and appearance (AbdAlmageed et al., ; Chen, Patel, & Chellappa, ; Ranjan, Sankaranarayanan, Castillo, & Chellappa, ; N. Zhang et al., ). This is a consequence of the fact that DCNN architectures for face identification are trained on large numbers of identities and use multiple, variable images of each identity.…”
Section: Introductionmentioning
confidence: 99%
“…For face identification, a major accomplishment of DCNNs is their visual robustness to changes in viewpoint, illumination, expression, and appearance (AbdAlmageed et al., ; Chen, Patel, & Chellappa, ; Ranjan, Sankaranarayanan, Castillo, & Chellappa, ; N. Zhang et al., ). This is a consequence of the fact that DCNN architectures for face identification are trained on large numbers of identities and use multiple, variable images of each identity.…”
Section: Introductionmentioning
confidence: 99%
“…The higher the values are, the better the performance is. We compare four pooling methods including scoremax [25], score-average [26], [28], feature-average [11], [12], [13] and kNN-average pooling based on three different metrics. ROC curves are drawn for each setting in Fig.…”
Section: B Ijb-a Evaluationmentioning
confidence: 99%
“…In this case, besides the old problem of how to extract invariable and discriminative features, finding a solution to match two sets of media is also challenging. Most of the existing methods until now mainly include feature pooling [11], [12], [13] and score pooling [25], [26], [28], where the former suggests aggregating features over all images in a set while the latter aggregates the pair-wise similarity scores of two compared sets. However, neither of the two measurements performs well when the faces of certain subjects are with many extreme poses or other variations, which occur frequently in reality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the experiments in [10] have shown that it has got a bad performance in AR sunglass image set, only achieving less than 50% recognition rate. Wael AbdAlmageed et al [13] use several pose specific deep convolution neural network (CNN) models to generate multiple pose-specific features. Jun-Cheng Chen et al [14] present an algorithm for unconstrained face verification based on deep convolution features, and obtain a good recognition result on the occasion with pose variations.…”
Section: Related Workmentioning
confidence: 99%